Strategic management - Lynch, Richard L. (SAGE, 2021)
"The 9th edition of Strategic Management offers comprehensive coverage of all the core areas of business strategy with a strong global perspective. Key features: balanced coverage of prescriptive and emergent models of strategic management; application of strategic theory to new areas including technology and innovation strategy, sustainability and green strategy, entrepreneurial strategy and public sector strategy; major revisions to chapters on Strategic Purpose, Knowledge and Networks, Theories of Entrepreneurship and International and Global Strategy in line with key developments; 20 brand new cases and updated case material throughout exploring the shifting economic fortunes of companies around the world, the rise of developing nations and rapid changes in communications and technology including the impact of the Corona virus; range of tools within the book and online to support your learning including key strategic principles, strategic project ideas, critical reflections, questions and further reading." -- Provided by publisher.